Peran Nilai Pelanggan Memediasi Pengaruh Kualitas Pelayanan Dan Citra Merek Terhadap Keputusan Menginap - Ade Tri Saputra; Rivera Pantro Sukma (LPPM and Travel Operation Department Universitas Asa Indonesia, 2023)
The purpose of this study is to determine the influence of service quality and brand image on decision to stay through customer value. The sampling technique uses accidental sampling method as many as 148 respondents. Data processing conducted by this study uses SmartPLS application version 3.2.9. The results of this study, there is a significant direct influence of service quality on customer value, service quality has a positive and significant effect on decision to stay, brand image has a positive and significant effect on customer value and brand image has a significant positive effect on decision to stay and for indirect influences, service quality through customer value has a significant effect on decision to stay, Also, brand image through customer value has a significant influence on decision to stay.